Principles and Methods for Describing Social Vocabulary in the Ideographic Dictionary - A. V. Shchetinina; A. N. Blinova (Научный диалог)
Questions of ideographic description and lexicography of social vocabulary are considered. It is shown that in spite of a considerable number of works devoted to the study of different groups of social vocabulary, a comprehensive description of social nominations is currently lacking. On the example of the analysis of nominations representing institutional relations, a technique for analyzing vocabulary is developed and improved in terms of the actualization of social semantics in linguistic units. It is noted that the relevance of the work is due to the comparative perspective of the study, since the vocabulary is drawn from different idioms of the Russian language: literary language, jargon, urban vernacular and Russian folk dialects - in order to establish discrepancies and similarities between the consciousness of Russian speakers representing different social, territorial and other groups. The practical significance and perspective of research consists in the creation of an ideographic description of social vocabulary in the form of an ideographic dictionary. On the example of the analysis of the nomination banderovets ( Banderaers ), the logic of the formation of new meanings of words not previously fixed by dictionaries and the creation of dictionary articles for the ideographic dictionary is justified. Application of methods of semantic, classificatory, linguistic-statistical, contextual, definitional analysis is demonstrated and also the method of ideographic reconstruction of nominative sets is partially presented.